2016
DOI: 10.1002/pits.21987
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Predictors of Self-Determined Actions in Students With and Without Intellectual Disability

Abstract: Research in the field of intellectual disability suggests that promotion of self‐determination triggers positive transition outcomes for youth with intellectual disability. This article examines the contributions of personal and environmental variables in predicting self‐determined action in students with and without intellectual disability. The Spanish pilot versions of the Self‐Determination Inventory and the AIR Self‐Determination Scale were administered to 114 youth with and without intellectual disability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 34 publications
(50 reference statements)
2
9
0
Order By: Relevance
“…Self‐determination develops over the lifespan through person–environment interactions that satisfy psychological needs (Deci & Ryan, ; Grolnick, Deci, & Ryan, ) and support component behaviours and attitudes of causal agency (Wehmeyer, Shogren, Little, & Lopez, ). People with intellectual and developmental disabilities (IDD) tend to report lower levels of self‐determination than do their peers without disabilities (Mumbardó‐Adam, Shogren, Guàrdia‐Olmos, & Giné, ; Wehmeyer & Metzler, ) and with learning disabilities (Chou, Wehmeyer, Palmer, & Lee, ; Seong, Wehmeyer, Palmer, & Little, ). Although cognitive ability may impact the support needed to develop and express self‐determination, socioecological factors are essential for understanding this difference (Shogren, ; Wehmeyer et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Self‐determination develops over the lifespan through person–environment interactions that satisfy psychological needs (Deci & Ryan, ; Grolnick, Deci, & Ryan, ) and support component behaviours and attitudes of causal agency (Wehmeyer, Shogren, Little, & Lopez, ). People with intellectual and developmental disabilities (IDD) tend to report lower levels of self‐determination than do their peers without disabilities (Mumbardó‐Adam, Shogren, Guàrdia‐Olmos, & Giné, ; Wehmeyer & Metzler, ) and with learning disabilities (Chou, Wehmeyer, Palmer, & Lee, ; Seong, Wehmeyer, Palmer, & Little, ). Although cognitive ability may impact the support needed to develop and express self‐determination, socioecological factors are essential for understanding this difference (Shogren, ; Wehmeyer et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there is a dearth of literature focused on self-determination in YA-ASD (Carter et al, 2009; Chou et al, 2017a; Chou, Wehmeyer, Shogren, Palmer, & Lee, 2017b; Wehmeyer, Shogren, Zager, Smith, & Simpson, 2010). Several studies examining self-determination in people with ASD and/or intellectual disability found variations in self-determination that were predicted by intellectual disability, educational setting, disability severity, and age (Carter et al, 2013a, 2013b; Mumbardó-Adam, Shogren, Guàrdia-olmos, & Giné, 2017b). The vast majority of these studies include only a subsample of children or adolescents with autism, leaving a large gap in our understanding of how to best assist YA-ASD in building self-determination skills.…”
mentioning
confidence: 99%
“…[ 15 , 16 , 17 , 18 ] made a discriminant function analysis of predictors of self-determination scores, showing that only perception of choice opportunity (from among four variables, including IQ) predicted membership in the group of participants with high self-determination scores. Likewise, previous studies [ 39 , 40 , 41 , 42 , 43 ] have also described opportunities for self-determination as significant predictors of self-determined actions. Interestingly, the autonomy domain has been shown to be influenced by opportunities at home but not in other environments, in line with recent studies where data was collected directly amongst participants with ID [ 23 ]; thus, stressing this shared perspective.…”
Section: Discussionmentioning
confidence: 75%